Development of monitoring system for mentor-mentee programme - Norhamidi, Noralia Hazira; Abu Hanifah, Mohd Shahrin; Zulkurnain, Nurul Fariza; Ab Rahim, Rosminazuin (IEEE, 2023)
Currently, the mentor-mentee programme (MMP) in Kulliyyah of Engineering (KoE), International Islamic University Malaysia (IIUM) is running as usual throughout every semester. However, the academic advisor found that there were several weaknesses that can be improved by developing an online monitoring system. The system can monitor the progression of every student and offer a helping hand. It also can save information about the mentee’s development so that academic advisor will ensure all the students are being assisted. Therefore, the primary objective of the project is to focus on the mentees who are facing some troubles and guide them through the process. This project is aimed to develop a web-based monitoring system, Mentor-Mentee Programme Online Monitoring System (MMPs) with the utilization of database management system that is used to track mentor-mentee relationships. This work shows the MMP system is developed using language of PHP technology and the development tools used visual studio code and java script language. The backend database is supported by MySQL language, which is built into the system.